In vitro physicochemical properties and antioxidant capacity of the aqueous extract of Gentianella nitida - Carbonel Villanueva, Kelly Nora (2016)
Introduction. The Gentianella nitida (hercampuri) is used as a hepatoprotective agent in traditional medicine. Objective. To determine the in vitro physiochemical properties and antioxidant capacity of the aqueous extract of Gentianella nitida. Design. Observational, analytical study. Setting. Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Material. 4% (w/v) of aqueous extract of the whole plant of Gentianella nitida from Junin. Interventions. Observation and analysis of the in vitro physicochemical properties and antioxidant capacity. Main outcome measures. Physicochemical properties (apparent density and soluble matter); antioxidant capacity using DPPH, ABTS and FRAP; total phenols content and flavonoids. Results. The Gentianella nitida presented an apparent density of 1,032 g/mL. With the DPPH and ABTS methods it had IC50=145 ug/mL and 1.49 ug/mL respectively; the antioxidant capacity equivalent to the ascorbic acid (AAEAC-DPPH) was 56 (ug AA/mg ss) and the antioxidant capacity equivalent to the trolox (TEAC-ABTS) was 87.7 (μg trolox/mg ss). Expressed in Frap, these were 98.5 (μg FeSO4/mg ss) and 55.6 (μgEAA/mg ss). The total phenolic content was 65.8 ug EAG/mg soluble solid and flavonoids was 11.7 ug EQ/mg soluble solid. Conclusions. The aqueous extract of Gentianella nitida exhibited antioxidant capacity that correlated with the content of phenolic compounds.